Accuracy of Dietary Assessment Methods as a Measurement of Micronutrient Intake in Adolescents: Scoping Review - Abdul Malik Simatupang; Yulia Lanti Retno Dewi; Tri Rejeki Andayani (Amerta Nutrition)
Background: Micronutrient deficiency, including iron, vitamin A, B-12 and folic acid, can cause anemia and harm adolescent health. Accurate dietary assessment methods is crucial to detect micronutrient deficiencies, but existing methods, have limitations, necessitating a review to identify the accurate methods for assessing micronutrient intake in adolescents.